Overcoming Barriers to Women's Career Transitions: A Systematic Review of Social Support Types and Providers - Greer, Tomika W.; Kirk, Autumn F. (Frontiers in Psychology, 2022)
In the current career landscape and labor market, career transitions have become a critical aspect of career development and are significant for Human Resource Development (HRD) research and practice. Our research examines the type of support used during different career transitions and who can provide that support to women in career transition. We investigated four types of social support – emotional, appraisal, informational, and instrumental – and their roles in five types of career transitions: school-to-work transition, upward mobility transition, transition to a new profession, transition to entrepreneurship, career re-entry transition, and transition to retirement. We analyzed 80 journal articles using directed content analysis, cross-tabulation, and nonparametric statistical tests. Instrumental support appears to be the most commonly documented type of social support in this career transition literature. Appraisal support was consistently documented least for each type of career transition. Our results may highlight the importance of personal connections and internal resources in successful career transitions for women. Based on our findings, we offer a model of women’s social support network for career transitions and advocate for expanded networks of social support for women anticipating and during career transitions. The results of our study contain insights for how women can be supported in transitioning to the next career experience. We conclude with suggestions for future research.